Fertility of frozen buffalo semen in rural western Maharashtra - BHOSREKAR, M R; MAZKORI, R C; RANE, R S (The Indian Journal of Animal Reproduction, 2003)
Frozen semen was used for breeding buffaloes in the rural areas through buffalo breeding centres managed by trained Para veterinarians and veterinary officers. 18 such centres situated in 5 taluks of Sangali district were taken where AI was carried out. The records of bull mother farm at Bhilawadi station were also analyzed for conception rate. There was significant difference between centres and months for conception rates.